An Analysis of inter-dialectal homonyms between Sasak Meno-Mene and Ngeto-Ngete dialects triggering communication misunderstandings - Mutiah Ramadani Putri; Baiq Rismarini Nursaly; Siti Ariyani Rujiyah; Lina Puspita; Hastutik Hastutik; Nurlaili Hafizah (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study examines inter-dialectal homonyms in the Sasak language, particularly between the Meno-Mene and Ngeto-Ngete dialects, and their potential to trigger communication misunderstandings among speakers. Previous studies on Sasak dialects have predominantly focused on phonological and lexical variations, while semantic differences involving homonymous lexicons across dialects remain underexplored. Therefore, this research aims to identify and analyze homonymous vocabularies shared by the two dialects and explain their implications for inter-dialectal communication. This study employed a qualitative descriptive method. The data consisted of oral utterances collected from native speakers of the Meno-Mene dialect in Sakra Selatan Village and the Ngeto-Ngete dialect in Kerongkong Village, East Lombok, as well as supporting written sources from relevant literature. Data collection was conducted through observation, interviews, and documentation techniques, while the data were analyzed using contextual semantic analysis. The findings reveal twenty homonymous lexicons that share identical phonological forms but convey different meanings in each dialect. These semantic discrepancies frequently lead to misunderstanding and ambiguity in daily communication among speakers from different dialectal backgrounds. The study demonstrates that identical lexical forms do not necessarily represent identical meanings across dialects, highlighting the importance of dialectal competence and contextual understanding in maintaining effective communication. This research contributes to the study of semantics and dialectology by providing insights into inter-dialectal semantic variation in the Sasak language and supporting regional language preservation efforts.